2014
DOI: 10.1021/ef5011379
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Removal Mechanism from Municipal Solid Waste Using Steam with Various Temperatures

Abstract: With a goal to develop a suitable refuse derived fuel (RDF) manufacturing process, organic and inorganic chlorine removal from RDF was investigated by using steam with various temperatures. For organic chlorine pyrolysis, steam temperature was changed from 463 to 573 K. For inorganic chlorine removal by steam condensation, steam temperature was fixed at 373 K. The pyrolysis kinetics of organic chlorine increased with an increase in superheated steam temperature, whereas the chlorine emission kinetics increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Dai et al 18 achieved a 90% reduction in chlorine release at 1000 °C by adding MgCO 3 with 10% of the total waste mass consists.PVC: (CH 2 CHCl) n → n HCl + n C 2 H 2 NaCl: 2NaCl + SO 2 + 0.5O 2 + H 2 O → Na 2 SO 4 + 2HClNaCl: 2NaCl + H 2 O + m SiO 2 → Na 2 O· m SiO 2 + 2HClIn summary, the previous studies have primarily focused on chlorine release characteristics during RDF combustion, with factors such as temperature, time, waste composition, and additives being considered. 19–23 However, there is a lack of research on the impact of RDF particle granulation on chlorine release. The MSW without granulation is loose and the contact between components is insufficient, resulting in the low conversion rate of some solid–solid reactions and gas–solid reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al 18 achieved a 90% reduction in chlorine release at 1000 °C by adding MgCO 3 with 10% of the total waste mass consists.PVC: (CH 2 CHCl) n → n HCl + n C 2 H 2 NaCl: 2NaCl + SO 2 + 0.5O 2 + H 2 O → Na 2 SO 4 + 2HClNaCl: 2NaCl + H 2 O + m SiO 2 → Na 2 O· m SiO 2 + 2HClIn summary, the previous studies have primarily focused on chlorine release characteristics during RDF combustion, with factors such as temperature, time, waste composition, and additives being considered. 19–23 However, there is a lack of research on the impact of RDF particle granulation on chlorine release. The MSW without granulation is loose and the contact between components is insufficient, resulting in the low conversion rate of some solid–solid reactions and gas–solid reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the previous studies have primarily focused on chlorine release characteristics during RDF combustion, with factors such as temperature, time, waste composition, and additives being considered. [19][20][21][22][23] However, there is a lack of research on the impact of RDF particle granulation on chlorine release. The MSW without granulation is loose and the contact between components is insufficient, resulting in the low conversion rate of some solid-solid reactions and gas-solid reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Superheated steam has an excellent heat transfer property due to the addition of radiation heat transfer compared with heated air and nitrogen, and the treatment under ordinary pressure permits to reduce the operating cost relatively. It was successfully 6 applied to the dechlorination treatment of municipal solid waste (MSW) [42,43] and incineration ash [44]. Fonseca et al [45] investigated the effect of mixed gas of superheated steam and nitrogen without catalyst/adsorbent on the dehydrochlorination of PVC resin and indicated that the dehydrochlorination rate increased from 61 % (100 vol% nitrogen) to 77 % (50 vol% superheated steam -50 vol % nitrogen) at 523 K by adding superheated steam in nitrogen gas.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some of the authors carried out the dechlorination of refuse-derived fuel (RDF), , chlorides in incineration ash, and the carbonization of biomass by superheated steam, which has gained much attention as a result of the simplicity of the equipment and the higher heat transfer property. The effects of superheated steam on the dechlorination and the additives were not clear in these studies.…”
Section: Introductionmentioning
confidence: 99%